Theoretical study of the stability and properties of magic numbers (m = 5, n = 2) and (m = 6, n = 3) of bimetallic bismuth‐copper nanoclusters; Bim Cun. Issue 24 (11th August 2017) - Miralrio, Alan; Hernández‐Hernández, Arturo; Pescador‐Rojas, Jose A.; Sansores, Enrique; López‐Pérez, Pablo A.; Martínez‐Farías, Francisco; Rangel Cortes, Eduardo
Abstract: Inspired by the experimental discovery of magic numbers we present a first study using density functional theory for the structure and properties of neutral and cationic Bi6 Cu3 and Bi5 Cu2 clusters. Our results confirm predictions based on Wade's rules. The closed electron shells, characteristic of cationic clusters help impose enhanced stability, while also complying with Wade's rules. Charge distribution analysis, as well as electrostatic potential maps show that in almost all cases, Bi atoms donate charges to Cu atoms. According to the analysis of condensed Fukui indices, Cu atoms inside both clusters are not reactive. Contrastingly, Bi atoms are reactive and may be targeted by different types of attack. This study of the electronic properties may thus help to determine experimental strategies with the capacity to enhance the synthesis of catalysts. Abstract : The neutral and cationic bimetallic clusters Bi5 Cu2 and Bi6 Cu3 have magic numbers of atoms complying to Wade's rules. The cluster structures proposed previously based on these rules are confirmed by first‐principles calculations. Cationic clusters have larger formation energies, as consistent with their observed high abundance. According to Fukui indices, Cu atoms inside both clusters are not reactive, while Bi atoms may be the target of different attacks.